DINÁMICA DE LA REGENERACIÓN DE PASTIZALES ALTOANDINOS TRAS UN INCENDIO EN PUNO, PERÚ - Terroba Quispe, Nicaela Pilar (2026)
The stability of high Andean grasslands in light of climate variation and the interaction between drought and uncontrolled fires are of considerable interest. The objective of the study was to evaluate the effect of fire on vegetation cover distributed in functional groups and grassland productivity. Field assessments and monitoring were carried out using spectral indices (NBR, SAVI, and NDVI) from Sentinel 2. The assessments were carried out after an uncontrolled fire in November 2022 in Cancharani (site 1) and Yanamayo (site 2) at an elevation of 4 112 and 4 047 meters above sea level, respectively, in Puno, Peru. Fifty-one species were recorded, with the largest number found in the herbaceous and grass groups in both burned and unburned sites. The dominant species was Festuca dollichophylla, which is important for livestock feed. This species and other grasses proved resilient to disturbances such as drought and fire, probably due to their morphological characteristics. The unburned sites showed greater vegetation cover (77.8% and 83.3%, sites 1 and 2, respectively), higher biomass productivity (p < 0.05), and greater amounts of mulch. On the other hand, the regenerative dynamics of the burned grasslands did not recover to pre-fire levels, compared to the unburned areas. Spectral indices showed the dynamics of the vegetation state before and after the fire, showing a drop in values after the fire and recovery throughout the analysis period, with the NBR index showing the greatest sensitivity to the occurrence of the fire. The fire was of low severity but spread rapidly, causing minor alterations to the grassland